Phylogenetic and evolutionary relationships in selected Pinus species using rbcL and matK chloroplast genes - Lav Singh; Pooja Dixit; Ravi Prakash Srivastava; Shivaraman Pandey; Arpit Singh; Praveen Chandra Verma; Gauri Saxena (Open Journal of Plant Science - Peertechz Publications, 2021)
The genetic diversity of Pinus plants has been assessed in various phylogenetic studies that reveal the polymorphism directly at DNA levels. The rbcL and matK are the most commonly used markers for phylogenetic studies of Pinus sp. that exhibit a diverse geophysical adaptiveness and geographical variations across different regions as a result of genotypic modifications. This study evaluated usefulness of rbcL and matK genes for molecular identification and phylogenetic study among various species of Pinus. Maximum Likelihood (ML) and Neighbor Joining (NJ) analysis of the data obtained from rbcL gene belonging to ten Pinus species revealed four clusters. First Cluster included P. Wallichiana (PW), P.Elliottii (PEl) and P.Greggii (PG). Second cluster included P. Thunbergii (PT), P. Echinata (PE) and P.merkusii (PM). Third cluster included P.taeda (Ptd) and P. khasya (PK) while fourth cluster included P. Roxburghii(PR) and P. patula (PP). Similarly ML and NJ analysis of the data obtained from matK gene belonging to ten Pinus species revealed four cluster and one outgroup. First Cluster included P. Thunbergii (PT), P.Greggii (PG) and P.Elliottii (PEl) Second cluster included P. roxburghii(PR) and P.merkusii (PM)P. Echinata (PE) and third cluster included P. Wallichiana (PW) and P.taeda (Ptd) while fourth cluster included P. Patula (PP) and P. Khasya (PK). P.echinata remained out clustered in this analysis.